Preventing violence by intimate partners in adolescence: an integrative review - Rebeca Nunes Guedes De Oliveira; Rafaela Gessner; Bianca de Cássia Alvarez Brancaglioni; Rosa Maria Godoy Serpa da Fonseca; Emiko Yoshikawa Egry (SciELO, 2016)
Abstract OBJECTIVE To analyze the scientific literature on preventing intimate partner violence among adolescents in the field of health based on gender and generational categories. METHOD This was an integrative review. We searched for articles using LILACS, PubMed/MEDLINE, and SciELO databases. RESULTS Thirty articles were selected. The results indicate that most studies assessed interventions conducted by programs for intimate partner violence prevention. These studies adopted quantitative methods, and most were in the area of nursing, psychology, and medicine. Furthermore, most research contexts involved schools, followed by households, a hospital, a health center, and an indigenous tribe. CONCLUSION The analyses were not conducted from a gender- and generation-based perspective. Instead, the scientific literature was based on positivist research models, intimately connected to the classic public healthcare model and centered on a singular dimension.